Pacing behavior development: the role of task experience and the presence of competitors - Menting, S. G. P.; Khudair, M.; Elferink-Gemser, M. T.; Hettinga, F. J. (Medicine & Science in Sports & Exercise, 2025)
Introduction Self-regulation of effort during exercise (i.e., pacing) is a determinant of exercise performance, which develops during childhood and adolescence. Yet the various aspects of pacing under development, such as the capability to use task experience and retain the task goal in the presence of other competitors, have remained relatively unexplored.